Essential Characteristics of Economic Security of Enterprises and its Definition (Economic journal of Lesya Ukrainka Volyn National University, 2017)
We considered the essential characteristic of economic security of an enterprise in that article. Economic security is a key prerequisite for the effective operation of the enterprise. The system of economic security of the enterprise is designed to predict, prevent the crisis state of the enterprise, and, therefore, should be the main element of enterprise management in the long term. Economic security of the enterprise is an extremely urgent task at the presentstage of transformation of the Ukrainian economic system and access to international economic markets. The purpose of scientific research is to reveal the whole essence of the concept of «economic security of an enterprise» and to determine the main components of the economic security of an enterprise.The methodology and scientific research is based on the use of modern, innovative methods of analyzing the theory of economic security of an enterprise.By assessing the level of economic security of an enterprise, it is possible to analyze the entire economic activity of an enterprise, determine its effectiveness, identify and neutralize all available internal and external threats, and also warn of possible dangers that may arise in the future.The main goal of the company's economic security should be to determine the most efficient operation of the enterprise as a whole, in particular, the full operation of the rapid response system of the operating system, the economical use of available resources, the high level of labor potential, the level of economic activity of the enterprise, the constant stimulation of the existing potential and its prospects for development. The main components of the study of the level of economic security of the enterprise can be characterized by its current state of security, the effectiveness of the activities carried out, the ability of the enterprise to develop in the future, that is, the interaction of the existing state with the established goals.At achievement of the objects in view, the enterprise must secure itself economic security; for this purpose, possible threats are investigated, all actions are taken to prevent real threats, threats are analyzed and assessed, decisions are taken to block and eliminate the threats, and the system of economic security is constantly improved.
Keywords: economic security of the enterprise, level of economic security, opportunities, internal and external threats, approaches to economic security research